Public awareness about infant prematurity and its related health issues: A national-based survey in Jordan - Reem Ali; Karimeh Alnuaimi; Buthyna Alnasarat (Clinical Epidemiology and Global Health)
Background: The incidence of premature birth is high in Jordan, with no significant lowering of figures seen during the past decades. The knowledge of the associated high morbidity and mortality rate among preterm infants makes prematurity a high priority for the healthcare system in Jordan. This study aims to assess public awareness about prematurity, preterm infants’ health challenges and developmental disorders. Methods: A national-based survey was employed to collected data on people's level of awareness. Online questionnaires were distributed across the country using proportional clusters protocol which was based on the geographical distribution of the population in Jordan. Results: 3048 Jordanians, aged from 18 to 77 years, completed the questionnaires; the majority of them were females and held married status. Results showed that 69.9 % of respondents gave a correct definition of prematurity. The average percentages of correct answers regarding the seriousness of prematurity, risks, and health and developmental problems were 71.5 %, 74.4 %, and 62.5 %, respectively. People generally failed to accurately identify premature infants’ long-term health and developmental problems. ANOVA results showed that the levels of awareness are significantly higher among people who have high family income (p < 0.001), are well-educated (p < 0.001), and employed in medical fields (p < 0.001). Conclusion: Educational initiatives are needed to enhance public awareness, particularly among the poor and less educated sectors of society. Lectures could be given by healthcare professionals at hospitals, and posted via social media, to educate people about prematurity and premature infants' health-related issues, with attention paid to infants’ long-term health and developmental problems.